The Geostrategic Conflict In The Middle East - Bassemail, Abdelkrarim (University of Eloued جامعة الوادي, 2021)
في سياق الدراسات الإقليمية ، يمكن اعتبار الشرق الأوسط منطقة متميزة في السياسة العالمية بسبب خصائصها الجغرافية والاقتصادية ، فضلاً عن طبيعة الفاعلين المحليين والقوى الدولية المؤثرة. كانت هناك عدة مستويات من الصراع بين القوى الكبرى والقوى العظمى ، وشهدت المنطقة عدة مستويات من القوة التي تحولت من القوة العسكرية إلى القوة الناعمة إلى القوة الذكية. الغرض من هذه الورقة البحثية هو استخلاص الأدوار الاستراتيجية للقوى العظمى، الولايات المتحدة وروسيا في الشرق الأوسط ، وإلقاء الضوء على مصادر القوة ومظاهر الصراع بين الولايات المتحدة وروسيا في المنطقة. In the context of regional studies, the Middle East can be considered a distinct region in global politics because of its geographical and economic characteristics, as well as the nature of local actors and influential international forces. There have been several levels of conflict between major powers and superpowers, and the region has seen several levels of power that have shifted from military power to soft power to smart power. The purpose of this research paper is to extract the strategic roles of the superpowers the United States and Russia in the Middle East, and to shed light on the sources of power and manifestations of the conflict between the United States and Russia in the region.
مقال
Keywords: الجيوستراتيجية؛ الشرق الأوسط؛ الصراع؛ القوة؛ الحرب; geostrategy; Middle East; conflict; power; war